A relação entre sistemas de compensação, mobilidade no trabalho e motivação: proposição de um modelo de avaliação - Ferreira, Degson (2016)
Rewards systems of organizations are factors that can influence and interfere in motivation, in satisfaction, in absenteeism of employees and in staff turnover, also known as or turnover. This paper discusses aspects of these factors using the educational segment, specifically a Higher Education Institution (HEI), to validate the model. Thus, this research aims to propose an instrument to assess how a system of compensation (pay and promotion) exerts influence on motivation, on satisfaction and on staff turnover intention in the work of individuals in an organization. For both, a theoretical reference is organized in a systematic way about the aspects concerning people's motivation, rewards systems of organizations, promotion opportunities, as well as those related to the turnover and absenteeism of the person at work, besides also addressing the studies related to the theme. Thus, the prospect of research in this research is qualitative and quantitative, descriptive stamp. It was adopted as a methodological procedure to carry out a survey of 290 teachers. As data collection instrument was used systematic observation spot, consultation documents in the institution's file and application of questionnaires containing besides closed or dichotomous questions type "yes" or "no", assertive to capture the perceptions of respondents using a Likert scale. The analysis and interpretation of data, performed using descriptive statistics such as factor analysis, independent t-test, ANOVA and multiple regression analysis, show that the research tool developed, after undergoing validity and reliability analysis, it presented himself as being composed of four constructs (compensation system characteristics, motivation, intention to turnover and job satisfaction) and seven dimensions (transparency, fairness and controllability of the compensation system, extrinsic and intrinsic motivation, intent to turnover and job satisfaction). The latter construct emerged as being exclusive of instrument proposed here, setting up this way, as a specific and unique contribution of this research. The analyzes also allow to point out that the perception of the transparency of progression opportunities and of the fairness remuneration system are the two independent variables that significantly affect almost all dependent variables (they have a positive significant effect on both the extrinsic and intrinsic motivation and on job satisfaction and a negative significant effect on the intention to turnover), with the exception of work absenteeism which is not affected by any of the compensation system characteristics. Among the independent variables that do not statistically significantly affect any of the dependent variables are the perception of the transparency of the remuneration system and of the controllability of progression opportunities. The variables fairness of progression opportunities and the controllability of the remuneration system does not have a significant effect on three dependent variables: intrinsic motivation, the intention of turnover and absenteeism from work. But these last two variables affect significantly two dependent variables: extrinsic motivation and job satisfaction. Also the results of the analysis of the relationship between progression and teacher motivation indicate that the amount of progressions made in the UFT is the independent variable that significantly affect positively the extrinsic motivation of the institution's teaching staff, with the exception of intrinsic motivation that is affected by this variable. The time elapsed since the last progression (progression last) has a statistically significant negative effect on the intrinsic motivation of the UFT’s teachers surveyed, indicating that the older the progress made by them, lower their intrinsic motivation. The time of the next expected progression (progression future) is another independent variable that exerts a statistically significant positive influence on the extrinsic motivation of the UFT’s teachers, while it does not affect their intrinsic motivation. The results of multiple regression allow to highlight yet that satisfaction with the internal conditions of the institution significantly negatively affects the intention turnover of UFT’s teachers surveyed, indicating that the more satisfied the UFT’s teachers are with the internal working conditions provided by institution, the less their will to resign and look for another job or other professional activity different from what they currently play.